Software-Defined Radios for Satellite Ground Stations : Literature Survey - Mwakyanjala, Moses (Luleå tekniska universitet, Rymdteknik, 2020)
This report presents a literature survery on software-defined radio (SDR) technology and commercial-off-the-shelf (CoTS) SDR frontends. The survey on SDR technology covers hardware components with special emphasis on signal processing devices. On the other hand, the survey on CoTS covers two SDR platforms that are considered for the development of a software defined satellite ground station. This development is part of a project jointly hosted by Luleå Tekniska Universitet (LTU) and the Swedish Space Corporation (SSC). It is titled "Advanced Software Dened Radio technology for new satellite ground equipmentarchitecture".